2014
DOI: 10.1108/joepp-05-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of leader justice and support for safety on safety performance

Abstract: Organizations may improve safety by hiring and promoting leaders who demonstrate a disposition toward treating their employees fairly, and by training leaders to inform employees about issues, policies and problems accurately and in a timely manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Other individual background variables such as age, gender, education, work experience, and work position were seldom included as the focus of study in the reviewed literature. Rather, they were usually treated as control variables (e.g., Kaufman et al, 2014;Xia et al, 2017). This finding is consistent with the review on causes of workplace safety violation (Alper and Karsh, 2009) and of safety performance in construction sites (Khosravi et al, 2014;Mohammadi et al, 2018).…”
Section: Personal Traitssupporting
confidence: 71%
See 1 more Smart Citation
“…Other individual background variables such as age, gender, education, work experience, and work position were seldom included as the focus of study in the reviewed literature. Rather, they were usually treated as control variables (e.g., Kaufman et al, 2014;Xia et al, 2017). This finding is consistent with the review on causes of workplace safety violation (Alper and Karsh, 2009) and of safety performance in construction sites (Khosravi et al, 2014;Mohammadi et al, 2018).…”
Section: Personal Traitssupporting
confidence: 71%
“…Furthermore, supervisors' support for safety and their general leadership can produce an interactive effect on worker safety behavior: leader justice, irrespective of context, was associated with lower safety performance when leaders were not supportive of safety (Kaufman et al, 2014). Supervisors who are considerate and open to workers' problems (i.e., open leadership) were likely to regard safety of their subordinates as important, which then increased workers' safety participation (Andriessen, 1978).…”
Section: Supervisor Influencementioning
confidence: 99%
“…For evaluating the structural model, researchers agreed that four main criteria include the R-square (R 2 ), the predictive relevance (Q 2 ), path coefficient (β), and effect size (F 2 ) (Hair , 2014;Hair et al, 2017;Hair et al, 2011;Lowry & Gaskin, 2014). However, a recent update in Smart PLS 4 removed the predictive relevance.…”
Section: Structural Modelmentioning
confidence: 99%
“…In addition, colleagues' behavior also impacts CWSB. Choudhry, et al [61] illustrated that some workers' unsafe behaviors originate from peer pressure. Liang, et al [62] also found construction workers' safety violations have social contagion effects.…”
Section: Critical Influence Factors Of Cwsbmentioning
confidence: 99%